Meta-analysis Reveals No Association of DNMT3B -149 C>T Gene Polymorphism With Overall Cancer Risk - Kumar Mandal, Raju; Haque, Shafiul; Wahid, Mohd; Jawed, Arshad; Akhter, Naseem; Ekhlaque Ahmed Khan, Md.; Kumar Panda, Aditya; Yahya Areeshi, Mohammed; Ahmad Dar, Sajad (Current Genomics, 2016)
Background: DNA methyltransferase-3B (DNMT3B) plays a key role in establishment and maintenance of genomic methylation patterns. Polymorphism in promoter region -149 C>T (C46359T) of DNMT3B gene may alter DNMT3B activity which leads to increased susceptibility to cancer. Inconsistent results regarding this have been reported in a number of studies. Objective: To carry out a meta-analysis of the studies reported to assess the precise relationship between the DNMT3B -149 C>T polymorphism and the overall cancer risk. Method: PubMed (MEDLINE) web database was searched for the studies concerning DNMT3B -149 C>T polymorphism and its association with cancer risk. The pooled odds ratios (ORs) along with 95% confidence intervals (95% CIs) were calculated for all the genetic models, from the selected case-control studies, by meta-analysis. Results: Overall eighteen studies containing 5583 cancer cases and 7618 controls were analyzed. No significant risk was observed overall for T allele carrier (T vs. C: p=0.303; OR=1.032, 95% CI=0.972- 1.097), homozygous (TT vs. CC: p=0.336; OR=1.063, 95% CI=0.939–1.204), heterozygous (CT vs. CC: p=0.802; OR=1.022, 95% CI=0.860-1.216), dominant (TT vs. CC+CT: p=0.298; OR=1.101, 95% CI=0.919-1.319) and recessive (TT+CT vs. CC: p=0.656; OR=1.021, 95% CI=0.931-1.121) genetic models. Subgroup analysis of Asian and Caucasian populations also did not demonstrate any cancer risk in all the genetic models studied. Conclusion: Our meta-analysis proposes that the DNMT3B -149 C>T polymorphism may not be an independent predisposing factor for the risk of cancer. However, larger sample size and expression studies are required to confirm the observation.
Keywords: Polymorphism